THE IMPACT OF AIR POLLUTION FROM PM2.5 DUST ON THE RESPIRATORY HEALTH OF URBAN POPULATIONS AND PREVENTIVE MEASURES - Sanwonglakron, Chatthasanan; Wareewarach, Ruangwit (Journal of MCU Nakhondhat, 2025)
Air pollution caused by fine particulate matter (PM2.5) poses a significant threat to public health worldwide, particularly affecting the respiratory system. These microscopic particles can penetrate deep into the lungs and enter the bloodstream, leading to inflammation of the respiratory tract and increasing the risk of various diseases such as asthma, chronic obstructive pulmonary disease (COPD), and lung cancer. Numerous studies have demonstrated a correlation between rising PM2.5 levels and a higher incidence of respiratory diseases, particularly among vulnerable groups, including children, the elderly, and individuals with pre-existing chronic conditions. The mechanisms through which PM2.5 affects health involve inflammatory responses, oxidative stress, and immune system alterations. Additionally, PM2.5 contains toxic substances, including heavy metals and carcinogens, which can damage lung epithelial cells and increase susceptibility to respiratory infections. Major sources of PM2.5 emissions include fossil fuel combustion from transportation and industrial activities, as well as biomass burning. Effective prevention strategies can be categorized into individual-level and policy-level measures: At the individual level, people should wear N95 masks, avoid outdoor activities during high pollution periods, and install air purifiers in indoor spaces. At the policy level, governments should enforce stricter air quality standards, regulate emissions from vehicles and industries, promote the use of clean energy, and expand urban green spaces to reduce airborne particulate matter. This study highlights the link between PM2.5 air pollution and the prevalence of respiratory diseases, while also proposing effective prevention strategies to mitigate health impacts. These findings can serve as a basis for policy development and practical measures aimed at improving air quality and reducing long-term health risks.